Peningkatan literasi numerasi siswa kelas 4 dengan math adventures berbasis problem-based learning - Sapruddin, Aisyara Zalzabila; Rahmawati, Fitri Puji; Hidayati, Yulia Maftuhah; Desstya, Anatri; Nisa, Choirun (Penamas: Journal of Community Service, 2025)
The “Math Adventures” program aims to improve the numeracy literacy of grade 4 students of SDN 02 Mancasan through a Problem-Based Learning approach. The program was designed using mixed methods, integrating pre-test, post-test, and interviews to evaluate its effectiveness. Interactive learning media such as flashcards, digital quizzes, and multiplication boards were used over three sessions to help students understand numerical concepts in a fun way. The results showed a significant increase in the student’s average score, from 70 in the pre-test to 83 in the post-test. In addition to improving their scores, the program also increased students’ motivation to learn mathematics and reduced their anxiety about the subject. The PBL approach effectively creates relevant, sustainable learning experiences that encourage critical thinking skills and problem-solving abilities. With interactive and collaborative methods, the program facilitates students’ understanding of numerical concepts and provides training teachers can adopt to create more engaging learning. This program is expected to be an innovative model that can be applied in other primary schools to holistically improve students’ numeracy literacy.